PENGARUH PRODUCT QUALITY , PRODUCT INNOVATION, DAN QUALITY OF SERVICE TERHADAP CUSTOMER LOYALTY DI BATIK DEWI KUNTI JEPARA - Trilala, Desi Cahya; Huda, Nurul (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This research aims to analyze the effect of product quality, product innovation, and quality of service on customer loyalty at Batik Dewi Kunti JeparaMethods: This research uses a quantitative approach with a survey method and data analysis using Partial Least Square (PLS). The research sample consisted of 94 respondents selected by purposive sampling.Results: The results showed that product quality, innovation, and service have a significant positive effect on customer loyalty. Product quality creates trust, innovation meets consumer needs, and superior service builds emotional relationships that increase customer satisfaction and commitment. The three factors simultaneously influence customer loyalty by 57%, while the other 43% is influenced by other variables not examined in this study. These findings provide strategic recommendations for Batik Dewi Kunti Jepara to continue to improve product quality, innovate according to market needs, and provide superior service to maintain customer loyalty in the midst of business competition. Keywords: Batik Dewi Kunti Jepara, Customer Loyalty , Product Innovation, Product Quality, Quality of Service